Epidemiological Trends of Leprosy in Rajshahi District (TAJ: Journal of Teachers Association, 2010)
This retrospective study was done in Rajshahi Medical College Hospital using the data from DOTS corner of Rajshahi Medical College Hospital. Study period was 2002 to 2008. According to proper clinical evaluation and slit skin smear results, patients were categorized into purely neuritic, tuberculoid, borderline tuberculoid, borderline, borderline lepromatous and lepromatous leprosy. In our study, we have found that number of leprosy cases has decreased substantially after 2004. Average case detection in the study period was 38.5 per year. Age group analysis has shown that no age group is exempted from the disease; quite a few cases have been described in the 1-9 year age group. Borderline tuberculoid (BT) leprosy was found to be the commonest form of leprosy in Rajshahi district. In fact, about 75% of the total leprosy cases were BT. Other forms of leprosy, in decreasing order of frequency, were LL, BL, TT, BB, and PN. Paucibacillary and multibacillary cases were almost equal in number. DOI: 10.3329/taj.v22i1.5025 TAJ 2009; 22(1): 88-92